Identification of two novel host proteins interacting with Toxoplasma gondii 14-3-3 protein by yeast two-hybrid system - Li, Fa-Cai; Liu, Qing; Elsheikha, Hany M.; Yang, Wen-Bin; Hou, Jun-Ling; Zhu, Xing-Quan (Springer, 2018)
Toxoplasma gondii deploys many effector proteins in order to hijack and manipulate host cell signaling pathways, allowing parasite colonization, subversion of immune responses, and disease progression. T. gondii effector protein 14-3-3 (Tg14-3-3) promotes parasite dissemination inside the body, by enhancing the migratory ability of infected microglia and dendritic cells. Understanding both the mechanism of action and the host targets of Tg14-3-3 effector is important because of their importance to the parasite’s virulence. The aim of the present study was to explore the function of Tg14-3-3 by utilizing the yeast two-hybrid system (Y2HS) to identify novel Tg14-3-3 interactors/substrates in host cells. A human cDNA library was screened using Tg14-3-3 as the bait. Tg14-3-3 (RH strain, Type I) was cloned into the pGBKT7 vector and expressed in the Y2HGold yeast strain. The bait protein expression was validated by Western blotting analysis, auto-activation, and toxicity investigation compared with control (Y2HGold yeast strain transformed with empty pGBKT7 vector). Two positive Tg14-3-3 interactors identified by this screening, hCG1821272 and eIF5B (eukaryotic translation initiation factor 5B), were isolated and characterized. This approach made it possible to gain a better understanding of the function of Tg14-3-3 in regulating host proteins involved in key cellular processes, such as translational initiation and cell migration.